Anthropometry Measurement Video Improve Knowledge of Cadres in Nganjuk City: A Single Group Pre-Post Test Design Study - Farah Paramita; Mika Vernicia Humairo; Septa Katmawanti; Nohan Arum Romadlona; Selsa Tri Septiani; Aqila Pakerti Nastiti; Putri Nurika Dewi; Ardi Bastian; Dian Mustikawangi (Preventia : The Indonesian Journal of Public Health, 2025)
High quality anthropometric measurements are important for nutritional assessment in children. In Indonesia, anthropometric measurement of children performed by caders in child center called posyandu as a child growth monitoring. However error measurements are found, especially on length or height measurement of children affecting presision and accuracy of data. This will lead to misinterpretation of child nutrition status. Education and training for cadres using media are important to improve their knowledge and skill related to anthropometric measurements. This study aimed to assess the effect of anthropometry measurement training using videos on Cadre’s knowledge. This study used one group pre-post test design with twenty cadres from Jekek and Mabung Village, Nganjuk City were recruited to this study. Intervention given to cadres was training using video anthropometry measurement. Knowledge score are measured before and after intervention. Statistical test was performed using paired t-test. The result of the study showed that there were significant different (p less than 0.05) of cadres’s knowledge score before (74.25 more or less than 7.48) and after training (78.75 more or less than 7.75). Anthropometric measurement training using video has effective in improving cadres knowledge of anthropometric measurement. Further study also needs to investigate skill improvement of anthropometric measurement for cadres.